Education of Hygiene Sanitation Processing Cane Water Traders as a prevention of Food Borne Disease Prevention - Siti Maisyaroh Fitri Siregar; Khairunnas Khairunnas (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2021)
The drink of freshly ground sugarcane from sugarcane stalks has a distinctive aoram, is cloudy in color and is sold without special packaging and is sold on the side of the road where the sanitation is very low so that its bacteriological quality is doubtful. Esherichia coli (e.coli) is a bacteria that can contaminate sugarcane juice. This research is about education on hygiene, sanitation, processing and examination of Escherichia coli (E.coli) bacteria in water drinks.,The most common drink in West Aceh is sugarcane water, this drink is very easy to find on the side of the road and is liked by every community.The purpose of this study was to see the effect of education on hygiene and sanitation of sugarcane water treatment and examination of Escherichia coli (E. coli) bacteria in sugarcane water.The research method used quasi-experimental and observational methods. The population in this study were sugar cane traders with a total sample of 20 people. The results showed that there was an effect of education on the sanitation hygiene of sugarcane water treatment and levels of Escherichia Coli (E.coli) in sugarcane water.